Odpowiedzi

  • Użytkownik Zadane
2010-01-18T19:02:23+01:00
(-2-1)do potęgi 3 +(-2-3)do p.3=-3³-5³=-27-125=-152
(-1)do .pot.8 -(-3)do pot.3-(-4)=1+27-4=24
(1/2)do pot.2 +(-1/2)do pot.3=1/4-1/8=2/8-1/8=1/8
-(2/5)do.pot.2 +(-1/2)do pot.2=-4/25+1/4=-16/100+25/100=9/100
(-3/4)do pot.2+(-1/2)do pot.3=9/16-1/8=9/16-2/16=7/16
(-2+1)do.pot .7+(-3-2)do.pot.2=-1+25=24
(-2-11)do.pot.2.-15do.pot 2=169+225=3375
2010-01-18T19:08:28+01:00
(-2-1) ³+(-2-3)³=-3³-5³=-27-125=-152
(-1)⁸-(-3)³-(-4)=1+27-4=24
(1/2)₂ +(-1/2)³=1/4-1/8=2/8-1/8=1/8
-(2/5)²+(-1/2)²=-4/25+1/4=-16/100+25/100=9/100
(-3/4)²+(-1/2)₃=9/16-1/8=9/16-2/16=7/16
(-2+1)⁷+(-3-2)²=-1+25=24
(-2-11)²-15²=169+225=337